Facile synthesis of lightweight carbonized hydrochars decorated with dispersed ZnO nanocrystals and enhanced microwave absorption properties. (September 2019) - Qi, Yujie; Qi, Lin; Liu, Liping; Dai, Bushi; Wei, Dongchao; Shi, Gui-Mei; Qi, Yang
Abstract: Application of heterostructures in electromagnetic interference shielding application has been limited by the issue of the uniformly and dispersity of composites. Herein, we synthesized carbonized hydrochars/ZnO nanocrystals (CH/ZnO) composites via a strategy of expanding the interface of heterostructure. The introduction of dispersed ZnO nanocrystals leads to the emergence of the special heterostructure, associated with significant interfacial polarizations, resulting in an upgraded microwave absorption properties. It is demonstrated that the optimized reflection loss can achieve −49.24 dB with the thickness of merely 1.24 mm, and effective bandwidth (less than −10 dB) is ranging from 13.2 GHz to 16.6 GHz. The CH/ZnO composites in this work are outstanding microwave absorber with the merits of lightweight, easy preparation, wide source of raw materials and low cost. Graphical abstract: Image 1